Pemanfaatan Limbah Beton Sebagai Bahan Stabilisasi Terhadap Penurunan Konsolidasi Tanah Lempung Kecamatan Sukodono Kabupaten Sragen - Fahelis, Davit, Qunik Wiqoyah, S.T., M.T, Agus Susanto, S.T., M.T (2017)
Based on Prasetyo (2016) Sukodono's soil is high plasticity inorganic soil, with LL 85.73%, PL 24.69%, and PI 61.04% (more than 17%). The road in that district has many damages such as potholes, cracks, distortion and also relatively short lifespan. In this research, waste concrete was used as stabilization material with mix percentage of waste concrete 5%, 10%, 15%, and 20% of the soil sample weight to find out the effect of the mix percentages toward the physical and mechanical properties of Sukodono's clay soil. The method of analysis in this research was including water content test, specific gravity, sieve analysis and hydrometer, Atterberg limits, standard Proctor and consolidation. The result of physical properties analysis of clay soil which is stabilized with waste concrete shows that the specific gravity value, water content, liquid limit, shrinkage limit, plasticity index, percentages passing sieve value No. 200, group index decreased, while plastic limit increased. The classification of the original soil and clay soil stabilized with waste concrete by AASHTO method belong to A-7-5 group, while based on the method of USCS original soil and soil stabilized with waste concrete percentage of 5% and 10% belong to the CH group while the soil stabilized waste concrete percentage of 15% and 20%, belong to MH. In the soil compaction test, the bigger percentages of the waste concrete mix, the maximum dry weight volume is increasing, while the optimum moisture content is decreasing. The results of consolidation test by increasing of the percentage of waste concrete, the Cv value (coefficient of consolidation) increased, thus the time required for consolidation is faster. The highest Cv value was obtained in 20% of waste concrete. Cc value (compression index) and Sc (settlement of consolidation) along with the increasing of the percentage of waste concrete mix decrease. Keywords: clay soil, consolidation, physical and mechanical properties, stabilization, waste concrete